Concurrent validity of an inertial measurement system in tennis forehand drive - Pedro, B.; Cabral, S.; Prieto Veloso, A. (Journal of Biomechanics, 2021)
The kinematic analysis in tennis forehand drive is crucial to understand the quality of this technique. The inertial measurement units (IMUs) due to its portability, occlusion free, larger capturing area and faster set up preparation, present an alternative to the optical motion capture systems (OS) considered a reference criterion system, however the degree of accuracy is task specific. This study aimed to compare the concurrent validity of a IMUs (Xsens MVN system) with an OS (Qualisys AB) for measuring upper and lower limb kinematics. Variables were evaluated during the forehand drive acceleration phase performed by 29 participants. The results demonstrated an excellent coefficient of multiple correlation (CMC) values (CMC = 0.95), for the majority of the variables with exception of shoulder in the anteroposterior plane (CMC: 0.85), and elbow in the axial plane (CMC: 0.79). Root-mean-square error (RMSE) were considered from good to tolerable (1.5° = RMSE = 6.7°), with exception of the elbow joint angle in transverse plane (RMSE: 13.1°). One dimensional (1D) statistical parametrical mapping (SPM) demonstrated good agreement between the two systems, with exception of elbow in transverse plane. The present work presents an important advancement to a more frequently use of the IMU`s in tennis, as well as in other racket sports.